Interaksi Antara Negara Dan Desa Adat Dalam Konstruksi Negara Kesatuan Republik Indonesia - Andress Deny Bakarbessy (SASI, 2018)
Indonesia is a unitary state that determines all regions of the country without exception constituting a unity of administrative and legal territory. However, in the territory of Indonesia there are also regions and unity of customary law communities, in this case the traditional village which has special characteristics that are special because it has existed before the formation of the State and has the right of origin in the administration of its government, and is recognized and respected by the State, so that the interaction between the State and customary villages allows conflicts between State law and customary law and traditions in the administration of government. For this reason, an ideal interaction between the State and the traditional village is needed which can create harmony and balance between the Country and the traditional village.